Indicadores de sustentabilidade no contexto da Política Nacional de Resíduos Sólidos: uma proposta para Bragança Paulista-SP - Camargo, Isadora Vilela de (2014)
Urban Solid Waste (USW) management represents an increasing challenge to municipal administration departments due to the growth in quantity of waste and complexity of its management. In Brazil, the National Solid Waste Policy (NSWP), approved in 2010, came to be a reference to local public policies, incorporating a concern with sustainability. Some authors have been proposing sustainability indicators (SI) to USW management since this sector needs tools to help with decision-making actions as well as with democratization of information to the society. However, these works neither consider the definitive content of NSWP, nor the strategic involvement of municipal councils related to the topic. This is important to assess how the conditions of these sustainability indicators match with the sustainability conditions brought by the policy. The aim of this present work was a proposition of a sustainability indicators set for solid waste management in Bragança Paulista-SP by means of consultation to the Municipal Environment Defense Council COMDEMA in the context of the NSWP. The research was based on interfaces assessment of three sets of SI for Solid Waste Management found in the literature with the NSWP. In order to facilitate this process, indicators were grouped in 15 topics, being detected their contribution and restrictions. This assessment, set on local context and researchers perceptions resulted in a proposal of a group of 25 SI which went through COMDEMA s consultation regarding relevance and form. On a second stage, new SI were developed, based on topics identified in the NSWP and were also consulted by the mentioned council. It was possible to ascertain that the NSWP incorporates dimensions of sustainability and many of its aspects are represented in the SI studied. This fact enforces the usefulness of this tool to a more sustainable solid waste management in local level. Nevertheless, to some recent topics such as reverse logistics, shared responsibility, Urban Solid Waste intermunicipal consortiums and recovery of organic solid waste, there were developed new indicators in order to get a more complete management. The final set resulted in 30 SI which meet the five dimensions of sustainability (environmental, social, economic, cultural and political) and include significant aspects of the NSWP as well as characteristic questions of the city. The involvement of COMDEMA, by its composition, engagement and interest, contributed to the access of information and members discussions, resulting in adjustments of the initial set, which include local demands. The experience of consultation adopted in this work, in order to propose SI to the SW management, can support future research, and may be adapted to the reality of other cities. The final SI set, which may come to be totally or partially incorporated to the Municipal Solid Waste Plan, can collaborate with execution of the NSWP in the city, leading it to a more democratic and sustainable management.